Process evaluation of the ACTION programme: a strategy for implementing person‐centred communication in home care - Tanja Gustafsson; Annelie J Sundler; Elisabeth Lindberg; Pernilla Karlsson; Hanna Maurin Söderholm (BMC, 2021)
Abstract Background There is currently a strong emphasis on person-centred care (PCC) and communication; however, little research has been conducted on how to implement person-centred communication in home care settings. Therefore, the ACTION (A person-centred CommunicaTION) programme, which is a web-based education programme focusing on person-centred communication developed for nurse assistants (NAs) providing home care for older persons, was implemented. This paper reports on the process evaluation conducted with the aim to describe and evaluate the implementation of the ACTION programme. Methods A descriptive design with a mixed method approach was used. Twenty-seven NAs from two units in Sweden were recruited, and 23 of them were offered the educational intervention. Quantitative and qualitative data were collected from multiple sources before, during and after the implementation. Quantitative data were used to analyse demographics, attendance and participation, while qualitative data were used to evaluate experiences of the implementation and contextual factors influencing the implementation. Results The evaluation showed a high degree of NA participation in the first five education modules, and a decrease in the three remaining modules. Overall, the NAs perceived the web format to be easy to use and appreciated the flexibility and accessibility. The content was described as important. Challenges included time constraints; the heavy workload; and a lack of interaction, space and equipment to complete the programme. Conclusions The results suggest that web-based education seems to be an appropriate strategy in home care settings; however, areas for improvement were identified. Our findings show that participants appreciated the web-based learning format in terms of accessibility and flexibility, as well as the face-to-face group discussions. The critical importance of organizational support and available resources are highlighted, such as management involvement and local facilitation. In addition, the findings report on the implementation challenges specific to the dynamic home care context. Trial registration This intervention was implemented with nursing assistants, and the evaluation only involved nursing staff. Patients were not part of this study. According to the ICMJE, registration was not necessary ().